Assessment of the capacity of cerebral collateral circulation using ultrasonic Doppler technique. Issue 11 (November 1975) - Tada, K; Nukada, T; Yoneda, S; Kuriyama, Y; Abe, H
Abstract : A new non-invasive method for the assessment of cerebral collateral circulation via the circle of Willis using an ultrasonic directional Doppler flowmeter is described. The technique was found useful in measuring the capacity of cerebral collateral circulation and would be applicable not only in internal medicine but also in neurosurgery.